Health statistics - Key data on health 2002 (Data 1970-2001) Luxembourg: Office for Official Publications of the European Communities, 2002 (Italian Journal of Public Health, 2004)
Since 1990s, the European institutions have been discussing on the importance to establish a HealthIndicators Monitoring System.This system would: undertake a “critical review of existing health data and indicators; develop appropriate methods for the collection of the progressively comparable health data needed to establish these indicators; develop a reliable system for the transfer and sharing of health data and indicators, essentially by means of the telematic interchange of data; identify methods and tools required for conducting analyses and producing reports on state of health, trends and determinants, and the impact of health-related policies” (according to the speech made by the European Commission representative, Mr. Frédéric Sicard, during the former EUPHA Conference held in Rome, last November).These are the outcomes of the Health statistics — Key data on health 2002, issued on March 8th 2004 and prepared by the Office for National Statistics (ONS), United Kingdom, and the sector ‘Health and safety’, of Unit E.3 (Education, health and culture) of Eurostat, on behalf of the European Commission.